(-7x^2)(6^x)-10x6^x=0

Printable View

- Jun 17th 2008, 10:46 AMArrazolo2007Solving exponential functions
(-7x^2)(6^x)-10x6^x=0

- Jun 17th 2008, 10:59 AMMoo
Hello !

$\displaystyle (-7x^2)({\color{red}6^x})-(10x)({\color{red}6^x})=0$

Factorising :

$\displaystyle 0=({\color{red}6^x})(-7x^2-10x)$

A product of factors is equal to 0 if and only if one of its factors is equal to 0, that is to say that if you have $\displaystyle ab=0$, then $\displaystyle a=0$ or $\displaystyle b=0$. But $\displaystyle 6^x \neq 0 \quad \text{for all x.}$

Therefore, $\displaystyle \dots=0$